Perbedaan Tingkat Dehidrasi Dan Kelelahan Pada Karyawan Terpapar Iklim Kerja Melebihi NAB (Stock Yard) Dengan Sesuai NAB (Produksi Jalur 2)Di PT. Wijaya Karya Beton TBK PPB Majalengka - Lestari, Sri (2016)
Industrial workers constitute the most fequent physical activity in hot work environments for a long time. Work climate that exceeds the threshold value can lead to health problems in workers such as dehydration and fatigue from loss of fluid through sweat and breathing. The purpose of this study was to determine differences in the level of dehydration and fatigue in employees exposed to the working climate >NAB with ≤NAB. This research method using observational analytic with cross sectional approach. The sampling technique used purposive sampling with a sample of 30 respondents. Analysis of data using statistical test Mann Whitney test and independent sample t-test with a significant level α = 0.05. The results showed that there are significant differences in the level of dehydration working climate>NAB with ≤NAB (p = 0.002). While the measurement of fatigue obtained results are not significantly different levels of fatigue at both location (p = 0.221). It can be concluded that the climate is hot work exceeds the NAB affect the incidence of dehydration, but has no effect on the occurrence of fatigue in workers.